FVC deterioration, airway obstruction determination, and life span in Ataxia telangiectasia. Issue 7 (July 2015) - Vilozni, Daphna; Lavie, Moran; Sarouk, Ifat; Bar-Aluma, Bat-El; Dagan, Adi; Ashkenazi, Moshe; Ofek, Miryam; Efrati, Ori
Summary Rationale Forced vital capacity (FVC) values decrease with progress of the disease in Ataxia telangiectasia (AT). Objective To study the effect of this process on airway obstruction determination and life span in AT. Methods Clinical data and yearly best spirometry maneuvers were collected retrospectively from 37 AT patients (196 spirometry tests) during 5.4 ± 1.8yrs (initial age 4–21 y). Twelve patients were walking (7 of them had recurrent respiratory system infections); 25 subjects were confined to wheelchair, of them 8 patients were towards end-stage lung disease. Spirometry indices included Forced Vital Capacity (FVC), mid-expiratory-flow (FEF25-75), and tidal volume (VT). We calculated FEF25-75/FVC and VT/FVC ratios. Results FVC declined from 67 ± 8 while walking to 19 ± 6 %predicted values. FEF25-75 values that were elevated (116 ± 23 %predicted) while walking, decreased to 69 ± 27 %predicted at end-stage where 7 patients responded to bronchodilators. VT/FVC ratio was 0.25 ± 0.06 while walking, increased to 0.35 once on wheelchairs, and further increased to 0.57 ± 0.19 at end-stage disease. FEF25–75/FVC ratio was 2.54 ± 0.70 above normal (∼1.0) increasing to 4.16 ± 0.75 at end stage. A sharp elevation was seen in FEF25–75/FVC ratio when FEV1 was still ∼45 %predicted and 2-years prior to death. Conclusions Having a low baseline-FVC (60% predicted) artificially raises FEF25-75 values, so FEF25-75 of "mild obstruction" values may indicate severe airway obstruction in AT subjects. VT/FVC and FEF25-75/FVC ratios may therefore assist in revealing higher than normal breathing effort. The results further suggest adding VT/FVC and FEF25-75/FVC ratios to pulmonary function assessments in patients with AT.